Entertainment industrialised the emergence of the international film industry, 1890-1940 - Bakker, Gerben (Cambridge studies in economic history. Second series, 2008)
Entertainment Industrialised was the first study to compare the emergence and economic development of the film industry in Britain, France and the United States between 1890 and 1940. Gerben Bakker investigates the commercialisation and industrialisation of live entertainment in the nineteenth century and analyses the subsequent arrival of motion pictures, revealing that their emergence triggered a process of incessant creative destruction, development and productivity growth that continues in the entertainment industry today. He argues that cinema industrialised live entertainment by automating it, standardising it and making it tradeable, a process that was largely demand led, and that a quality race between firms changed the structure of the international entertainment market. While a hundred years ago, European enterprises were supplying half of all films shown in the US, the quality race resulted in today's industry, in which a handful of American companies dominate the global entertainment business